Pelatihan Bahasa Inggris Pariwisata bagi Masyarakat Desa Rinding Allo - Magfirah Thayyib; Masruddin Masruddin; Zainuddin S.; Muh. Ilham Nur; Ermawati Ermawati; Andi Yuni Itami Idrus (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
With its diverse tourism potentials, Rinding Allo village has passed the top 75 of Indonesian Tourism Village Award in 2023 and is developing into an international tourist destination. The English language competences of people in an international tourist destination are very important to provide good service to foreign tourists. This training aims to provide the knowledge and skills of English for tourism for the people of Rinding Allo village. The method used in this community service program is Asset Based Community-driven Development which consists of six stages. The method was applied by integrating the needs analysis stages and the English for specific purposes learning approach. At the asset mobilization stage, English for tourism training was carried out for five meetings. Each meeting discussed one unit of the English for tourism module which had been specially compiled in the previous stages. English for tourism training for the people of Rinding Allo village run well and provided useful material for the participants. During the training, the participants seemed enthusiastic in learning and practicing tourism English conversation. The participants’ mastery of English vocabulary and expressions in the tourism context as well as their confidence in using the language in communicating increased through this training.